Breast-Milk Microbiota Linked to Celiac Disease Development in Children: A Pilot Study From the PreventCD Cohort - Benítez-Páez, Alfonso; Olivares, Marta; Szajewska, Hania; Pieścik-Lech, Małgorzata; Polanco, Isabel; Castillejo, Gemma; Nuñez, Merce; Ribes-Koninckx, Carmen; Korponay-Szabó, Ilma R.; Koletzko, Sibylle; Meijer, Caroline R.; Mearin, M. Luisa; et al. (Frontiers in Microbiology, 2020)
Coeliac disease (CeD) is an immune-mediated disorder triggered by exposure to dietary gluten proteins in genetically predisposed individuals. In addition to the host genome, the microbiome has recently been linked to CeD risk and pathogenesis. To progress in our understanding of the role of breastmilk microbiota profiles in CeD, we have analysed samples from a sub-set of mothers (n= 49) included in the PreventCD project, whose children did or did not develop CeD. The results of the microbiota data analysis indicated that neither the BMI, HLA-DQ genotype, the CeD condition nor the gluten-free diet of the mothers could explain the human milk microbiota profiles. Nevertheless, we found that origin country, the offspring's birth date and, consequently, the milk sampling date influenced the abundance and prevalence of microbes in human milk, undergoing a transition from an anaerobic to a more aerobic microbiota, including potential pathogenic species. Furthermore, certain microbial species were more abundant in milk samples from mothers whose children went on to develop CeD compared to those that remained healthy. These included increases in facultative methylotrophs such as Methylobacterium komagatae and Methylocapsa palsarum as well as in species such as Bacteroides vulgatus, that consumes fucosylated-oligosaccharides present in human milk, and other breast-abscess associated species. Theoretically, these microbiota components could be vertically transmitted from mothers-to-infants during breastfeeding, thereby influencing CeD risk.